1996
DOI: 10.1007/bf01857605
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the physical and psychosocial sequelae of bone marrow transplantation among long-term survivors

Abstract: We used a situation-specific approach to investigate common problems and associated coping processes among long-term survivors of bone marrow transplantation (BMT). Surveys were returned by 156 of the 191 (82%) eligible BMT survivors. Work and finance problems were endorsed relatively infrequently by respondents; physical problems and existential concerns were much more common. Problem occurrence was significantly related to demographic and treatment variables. The choice of coping mechanisms was related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 52 publications
2
19
0
1
Order By: Relevance
“…In agreement with previous studies [19], however, stress domains related to the physical impact of BMT such as "Side-effects", "Long-lasting treatment", and "Physical outcome" were perceived, on the average, as the most stressful, the least controllable, and were also experienced most often. Somerfield et al [19] also noted that interpersonal difficulties were the second most frequently reported concern.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In agreement with previous studies [19], however, stress domains related to the physical impact of BMT such as "Side-effects", "Long-lasting treatment", and "Physical outcome" were perceived, on the average, as the most stressful, the least controllable, and were also experienced most often. Somerfield et al [19] also noted that interpersonal difficulties were the second most frequently reported concern.…”
Section: Discussionsupporting
confidence: 89%
“…Somerfield et al [19] also noted that interpersonal difficulties were the second most frequently reported concern. In the present study, however, the stress cluster describing family-related stress was perceived as a separate and highly stressful domain.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies specific to survivors of leukemia and lymphoma, including Hodgkin's disease and non-Hodgkin's lymphoma, have identified medical and psychosocial outcomes such as a restricted role function at work and in daily activities, lack of energy, difficulties obtaining health insurance, education problems linked to missed school, and financial strain [15][16][17][18]. Others have identified concerns including anxiety, depression, cognitive impairment, and low rates of marriage and sexual activity [19,20].…”
Section: Quality Of Life For Long-term Cancer Survivorsmentioning
confidence: 95%
“…Results indicated that BMT survivors continued to have several debilitating physical symptoms 10 years following treatment, with fatigue rated as their second most problematic concern. 8 While several descriptive studies have indicated that BMT recipients frequently complain of fatigue, weakness, decreased energy and insomnia in their long-term recovery from BMT, 4,8,13,14,[20][21][22][23][24][25][26] most have not provided comparisons with normative samples. Two anomalous studies provide valuable insight into the experience of fatigue in BMT survivors.…”
Section: Physical Symptomatology and Fatiguementioning
confidence: 99%